Establishment and application of multiplex PCR method for detection of Trichophyton verrucosum, Microsporum canis, and Trichophyton mentagrophytes from cattle - Wang, Ya; Li, Zhiguo; Zuo, Zhicai; Gu, Xiaobin; Cai, Dongjie; Hu, Jianfeng; Gu, Yu; Shen, Liuhong; Gou, Liping; Zhang, Kun; Ma, Xiaoping (Frontiers in Veterinary Science, 2025)
IntroductionDermatophytosis, which is a contagious fungal skin infection common in animals and humans, is the most common skin disease in cattle. It has a serious negative impact on the livestock industry. In order to circumvent the shortcomings of traditional detection methods such as time-consuming and low isolation rate. Therefore, this study established a simple, rapid and effective diagnostic method to accurately diagnose and differentiate the causative fungi of dermatophytosis, which is of great significance to enhance the prevention and treatment of dermatophytosis in beef cattle farms.MethodsThree pairs of specific primers were designed using Primer Premier 5.0 from Trichophyton verrucosum, Microsporum canis and Trichophyton mentagrophytes. A triple PCR assay was established by optimising the primer dose and annealing temperature to improve the detection sensitivity. The feasibility of the method was verified by testing the samples.Results and discussionIn this study, a multiplex PCR method that can rapidly detect these three fungi at the same time was established, and its specificity, sensitivity and repeatability were analyzed at the same time. The results showed that the multiplex PCR method amplified the specific expected fragments of 581 bp, 1,513 bp and 371 bp for T. verrucosum, M. canis and T. mentagrophytes. The minimum detection limits of T. verrucosum, M. canis and T. mentagrophytes were all 1 pg./μL. The positive rates were 87.5% (21/24) for samples. The results showed that the multiplex PCR method was simple, specific and sensitive and might be used for rapid diagnosis and identification of dermatophytes in cattle.